Chemical Immunology and Allergy, 2005 2005
DOI: 10.1159/000087821
|View full text |Cite
|
Sign up to set email alerts
|

T Helper 1 and 2 Immune Responses in Relationship to Pregnancy, Nonpregnancy, Recurrent Spontaneous Abortions and Infertility of Repeated Implantation Failures

Abstract: It is becoming clear that during each developmental stage of pregnancy, different immunological conditions exist and may even be necessary for success. The widely accepted T helper (Th) 1 and 2 concept has some limitations if applied to the various developmental stages of pregnancy. During the implantation period, a multidirectional cytokine network is necessary with the blastocyst producing cytokines and other factors and the endometrium synthesizing factors necessary for the embryonic development. Improper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 66 publications
(81 reference statements)
2
60
1
6
Order By: Relevance
“…Such Th2 predominant response is the result of high levels of progesterone and oestrogen produced throughout all pregnancy [88]. The cytokine balance is directed toward a Th2 predominant response mainly after the second trimester of gestation [67] with strong Th1 immune responses during pregnancy resulting in maternal anaemia, spontaneous abortions and pre-term delivery [89].…”
Section: Specific Antimalarial Immunity During Pregnancymentioning
confidence: 99%
“…Such Th2 predominant response is the result of high levels of progesterone and oestrogen produced throughout all pregnancy [88]. The cytokine balance is directed toward a Th2 predominant response mainly after the second trimester of gestation [67] with strong Th1 immune responses during pregnancy resulting in maternal anaemia, spontaneous abortions and pre-term delivery [89].…”
Section: Specific Antimalarial Immunity During Pregnancymentioning
confidence: 99%
“…In several clinical situations, depending on the characteristics of each disease, such as AIDS 9 , cardiac 10 and neurological disorders 11 and in human reproduction 12 , a certain type of Th1/ Th2 immune response pattern is predominant. Our previous results showed that endometriosis is a complex disease with co-existence of both responses since we observed an increase in Interferon-gamma and IL-10 in patients with endometriosis when compared to a control group of patients without the disease 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This was evidenced by the association of increased Th2 cytokines with successful pregnancy, while heightened Th1 activity was indicative of poor pregnancy outcome, both in experimental animals and in humans (Hill et al 1995). In view of this interplay between (pro-inflammatory) Th1 and (anti-inflammatory) Th2 cells and their respective cytokines in pregnancy, dysregulated immunity stemming from altered Th1-Th2 balance was proposed as a potential mechanism underlying idiopathic RM in the face of unknown causes (Makhseed et al 2001, Kwak-Kim et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their pro-inflammatory and pro-apoptotic capacity, TNF-a and LT-a were described to mediate several aspects of pregnancy complications, including pre-eclampsia (Anim-Nyame et al 2003), miscarriage (Babbage et al 2001), and RM (Rezaei & Dabbagh 2002). Several mechanisms were proposed for the pro-abortogenic effects of TNF-a and LT-a, including trophoblast invasion and placentation (Kwak-Kim et al 2005) and induction of the expression of pro-apoptotic genes in human fetal membranes (Garcia-Lloret et al 2000), which in turn accelerates membrane degradation and thus increases the susceptibility to premature rupture (Fortunato et al 2001). TNF-a was also described to facilitate miscarriage indirectly by activating NK cells or macrophages (Raghupathy et al 2000).…”
Section: Introductionmentioning
confidence: 99%